A review of current logistics practice - Bytheway, Andrew (Cranfield University, 1995)
A review of the logistics and general literature reveals three forces at work which are changing the nature of global business: The globalisation of economies; The homogenisation of products; The advancement of technology Different sectors have a different level of awareness and achievement. Manufacturing is generally still somewhat inward looking, whereas retailing is the source of a good deal of innovation and change. In the United States the “Efficient Customer Response” initiative is a major factor in reshaping the channels of supply from manufacturing to retailing, and the distribution industry more than any other is suffering the effects of change. The more progressive participants in the distribution sector are trying to achieve a more dominant position, by offering a wider range of value-added services than simple transportation and storage of goods. The banking and payment clearing services sector is not seen as a major factor, despite the very significant opportunity to develop and improve payment services, and to link them more tightly with operational activity. The management of supply chain operations is becoming more sophisticated. Systems thinking, benchmarking and customer service imperatives are all causing a wave of new interest in the best ways to manage supply chain and logistics operations. The prospects for further significant developments in the future continue to expand, and it is difficult to see any limit or ultimate end to the development of logistics practices around the world.
A version of this paper has been published in "Global Logistics" - a Management Review puiblished by MCB University Press, Bradford, which also includes extensive abstracts from the logistics literature.
Keywords: Logistics; supply chain; logistics systems